2003
DOI: 10.1023/a:1024279831966
|View full text |Cite
|
Sign up to set email alerts
|

No variation for Wolbachia-induced hybrid breakdown in two populations of a spider mite

Abstract: Abstract. Wolbachia are cytoplasmically transmitted bacteria that infect several species of mites. In the two-spotted spider mite Tetranychus urticae Koch this symbiont can induce reproductive incompatibility. Wolbachia-induced reproductive incompatibility is observed in crosses between Wolbachia-infected (W) males and uninfected (U) females. This incompatibility is expressed in F1 broods as male-biased sex ratios, an effect called cytoplasmic incompatibility (CI). However, in the two-spotted spider mite, Wolb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(33 reference statements)
1
6
0
1
Order By: Relevance
“…Only in the phytoseiid Galendromus occidentalis (Nesbitt) and in some spider mites, the endosymbionts Wolbachia and more recently Cardinium have been demonstrated to mediate unidirectional reproductive incompatibility (Hess and Hoy 1982;Gotoh et al 1995;Johanowicz and Hoy 1996;Breeuwer 1997;Vala et al 2000Vala et al , 2002Vala et al , 2003Gotoh et al 2006;Ros and Breeuwer 2009). Bidirectional incompatibility is assumed to be caused by either negative nuclear-nuclear genes interactions, as has been reported in the spider mite Panonychus mori Yokoyama (Gotoh et al 2005), or infection by different strains of Wolbachia, as is well documented for insects (Laven 1959(Laven , 1967Mercot et al 1995;O"Neill and Karr 1990;Clancy and Hoffmann 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only in the phytoseiid Galendromus occidentalis (Nesbitt) and in some spider mites, the endosymbionts Wolbachia and more recently Cardinium have been demonstrated to mediate unidirectional reproductive incompatibility (Hess and Hoy 1982;Gotoh et al 1995;Johanowicz and Hoy 1996;Breeuwer 1997;Vala et al 2000Vala et al , 2002Vala et al , 2003Gotoh et al 2006;Ros and Breeuwer 2009). Bidirectional incompatibility is assumed to be caused by either negative nuclear-nuclear genes interactions, as has been reported in the spider mite Panonychus mori Yokoyama (Gotoh et al 2005), or infection by different strains of Wolbachia, as is well documented for insects (Laven 1959(Laven , 1967Mercot et al 1995;O"Neill and Karr 1990;Clancy and Hoffmann 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia can affect reproduction of spider mites and can cause CI in hosts, as in insects (Breeuwer 1997;Vala et al 2000Vala et al , 2003Perrot-Minnot et al 2002;Gotoh et al 2003Gotoh et al , 2005. On the other hand, there are many examples that Wolbachia infection does not induce any reproductive abnormalities to insect hosts (Hoffmann et al 1994(Hoffmann et al , 1996Giordano et al 1995) or to spider mite hosts (Gomi et al 1997;Gotoh et al 1999Gotoh et al , 2003Perrot-Minnot et al 2002;Xie et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…O’Neill et al , 1997; Stouthamer et al , 1999). Wolbachia has been detected in spider mites, and several studies have reported sex ratio alternation (Breeuwer, 1997; Vala et al , 2000, 2003a,b; Gotoh et al , 2003, 2005). Although most of these reported male‐biased sex ratio as cytoplasmic incompatibility, Vala et al (2000, 2003a) reported that infected females produced significantly more female‐biased sex ratios than uninfected (cured) females in T. urticae .…”
Section: Discussionmentioning
confidence: 99%